Peran Kegiatan Ekstrakurikuler Lembaga Pengembangan Tilawatil Quran (LPTQ) dalam Meningkatkan Prestasi Siswa di Madrasah Aliyah Swasta Muallimin UNIVA Medan - Aminy, Aisyah; Sinaga, Ali Imran; Sumanti, Solihah Titin (Kamaya: Jurnal Ilmu Agama, 2024)
Implementing This research aims to analyze the program, implementation of the Al-Quran Tilawatil Development Institute (LPTQ), the role of the madrasa head, deputy madrasa head, supervisors, trainers and teachers in LPTQ extracurricular activities as well as analyzing the supporting and inhibiting factors of the Development Institute's extracurricular activities (LPTQ). The method used in this research uses a qualitative method with a descriptive/analytic type. Data collection techniques used include interviews, observation and documentation studies. The data analysis techniques used include data collection, data reduction, data presentation, and drawing conclusions. The research results show that; 1) The extracurricular activities program of the Tilawatil Quran Development Institute which was developed at the Private Madrasah Aliyah Muallimin UNIVA Medan which consists of 4 branches, namely syarhil Quran, fahmil Quran, tilawatil Quran and khattil quran includes planning, implementation and evaluation of extracurricular activities. 2) The extracurricular activities of the Al-Quran Tilawatil Development Institute at the Muallimin Private Madrasah Aliyah UNIVA Medan are carried out once a week and last for two hours. 3) The role of the madrasa head, deputy madrasa head, supervisors, trainers and teachers in the extracurricular activities of the Tilawatil Quran Development Institute in improving student achievement at the UNIVA Medan Muallimin Private Madrasah Aliyah is to provide motivation, direct supervision and evaluation of existing extracurricular activities. 4) Supporting factors in the extracurricular activities of the Tilawatil Quran Development Institute at the Private Madrasah Aliyah Muallimin UNIVA Medan are human resources which include the head of the madrasa, deputy head of the madarsah, supervisors, trainers and teachers, facilities and infrastructure, as well as the interests and talents of each student. The inhibiting factors in the extracurricular activities of the Tilawatil Quran Development Institute at the Muallimin Private Madrasah Aliyah UNIVA Medan are the time factor and the curriculum factor in the madrasah.